Teachers’ perceptions and uses of generative artificial intelligence in Moroccan schools: Evidence from the Fez–Meknès region - Mohamed TIMMI; Ahmed BENAOUI (International Journal of Scientific Research and Innovative Studies, 2026)
This study explores how primary and secondary teachers in Morocco’s Fez–Meknès region understand and use generative AI in their classrooms. Most educators recognize generative AI as a powerful content‐creation tool and believe it can enrich lesson planning, personalize learning for diverse student needs, and support remote instruction. However, fewer have moved from interest to regular use, citing gaps in training and limited technical resources as the main obstacles. Teachers also express pragmatic concerns about data privacy and the importance of maintaining their instructional role alongside AI tools. Nearly all respondents welcome further hands-on professional development, particularly workshops and in-class coaching, to build confidence and practical skills. As schools prepare for a more AI-integrated future, these findings point to the need for targeted training programs, reliable infrastructure, and clear ethical guidelines that empower teachers to harness generative AI effectively and responsibly. Keywords: Generative AI, artificial intelligence, Teacher Perceptions, Professional Development, Classroom Integration, Ethical Guidelines, Educational Technology. Received Date: December 27, 2025 Accepted Date: January 12, 2026 Published Date: February 01, 2026 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/572